1993
DOI: 10.3758/bf03211165
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the processing view in accounting for dissociations among memory measures in a clinical population

Abstract: In three experiments, we examined the performance of patients with schizophrenia on implicit and explicit memory tests that have been shown to involve predominantly data-driven or predominantly conceptually driven processes. In Experiment 1, we compared the implicit tests of category production (conceptually driven) and word identification (data driven) and found that schizophrenic patients' performance on these tests did not differ from that of normal subjects. In Experiment 2, a comparison of the category-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 72 publications
2
39
0
4
Order By: Relevance
“…An alternative to the sensitivity account is based on the common assumption that spatiotemporal context plays a more important role in explicit than in implicit memory tests (e.g., Humphreys, Bain, & Pike, 1989;Jacoby & Dallas, 1981;Jacoby & Hollingshead, 1990;Light & LaVoie, 1993;Schwartz, Rosse, & Deutsch, 1993;see, also, Weldon et al, 1995). Under this view, conceptual explicit tests are sensitive to both prior conceptual processing and contextual encoding, whereas conceptual implicit tests are primarily sensitive to prior conceptual processing.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the sensitivity account is based on the common assumption that spatiotemporal context plays a more important role in explicit than in implicit memory tests (e.g., Humphreys, Bain, & Pike, 1989;Jacoby & Dallas, 1981;Jacoby & Hollingshead, 1990;Light & LaVoie, 1993;Schwartz, Rosse, & Deutsch, 1993;see, also, Weldon et al, 1995). Under this view, conceptual explicit tests are sensitive to both prior conceptual processing and contextual encoding, whereas conceptual implicit tests are primarily sensitive to prior conceptual processing.…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment that compared schizophrenics' performance on an explicit memory test (word recall cued by semantic categories) and an implicit memory test (semantic category-exemplar generation), Schwartz, Rosse, and Deutsch (1993) found that normal and patient groups obtained similar priming, but both groups were significantly different on word recall.…”
Section: Palabras Clave: Facilitación Memoria Implícita Esquizofrenmentioning
confidence: 99%
“…El hallazgo de que la recuperación basada en procesos automáticos es similar al grupo control coincide con los resultados hallados por anteriores estudios que emplearon tareas tradicionales de memoria implícita (Schwartz et al, 1993; Gras-Vincendon et al, 1994; Bazin y Perruchet, 1996). De manera similar vuelve a discrepar con los estudios de Randolph et al (1993), y Gold et al (1992b) al no hallar una merma de procesos automáticos en población esquizofrénica, también utilizando éstos tareas tradicionales de memoria implícita.…”
Section: Discussionunclassified
“…Concretamente en pruebas explícitas de memoria reciente sus rendimientos son defectuosos, ya se trate de recuerdo libre, con clave o serial, mejorándose los resultados en tareas de reconocimiento (Traupmann, 1975;Kietzman, Zubin y Steinhauer, 1984), y siendo, por último, equiparables sus rendimientos en tareas implícitas a los sujetos control (Gras-Vincendon, Danion y Grange,1994;Hurón, Danion, Giacomoni, Grange, Robert y Rizzo 1995;Bazin y Perruchet, 1996;Kazes et al, 1999;Besche-Richards, Passerieux, Hardy-Baylé, Nicolás y Laurent, 1999). Esta preservación en pruebas implícitas se ha mostrado tanto en tareas perceptivas, tales como identificación de palabras, como conceptuales en la tarea de evocación de ejemplos de categorías (Schwartz, Rosse y Deutsch, 1993). Sin embargo, y hasta la fecha, dos estudios no han encontrado una preservación absoluta de tal memoria en pacientes esquizofrénicos, bien en una tarea tradicional de completamiento de palabras (Randolph, Gold, Carpenter, Goldberg y Weinberger, 1993) o bien en tareas de estimación de frecuencias (Gold et al, 1992b).…”
unclassified